(untitled) (Journal of Atomic and Molecular Sciences, 2013)
The structural stability of nickel oxide (NiO)_n (n=1 7) nanoclusters were studied using Gaussian 03W program package with B3LYP/6-31G level basis set. It is observed that the ring structure is more stable in most cases compared to other structures( Linear and 3D). For n > 6 the 3D structure is no longer stable. From the optimization results of (NiO)_n clusters it is found that when the atoms in the cluster increases it leads to the increase in the stability. The dipole moment of each cluster is also studied which shows that the dipole moment depends upon the arrangement of atoms in the cluster. The HOMO LUMO gap, ionization potential, electron affinity and binding energies of Nickel Oxide clusters have been calculated and reported.